2012
DOI: 10.1088/0026-1394/49/4/522
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Cu(In,Ga)Se2thin films by secondary ion mass spectrometry using a total number counting method

Abstract: The relative atomic fraction of Cu(In,Ga)Se2 (CIGS) films is one of the most important measurements for the fabrication of CIGS thin film solar cells. However, the quantitative analysis of multi-element alloy films is difficult by surface analysis methods due to the severe matrix effect. In this study, the quantitative analysis of CIGS films was investigated by secondary ion mass spectrometry (SIMS). The atomic fractions of Cu, In, Ga and Se in the CIGS films were measured by alloy reference relative sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…RSF is calculated by integrating the total ion intensity from the D‐SIMS profile and dividing this value by the atomic concentration, which in turn was derived from the measurements of the atomic absorption spectroscopy (AAS) and inductively coupled plasma‐optical emission spectroscopy (ICP‐OES) (Table S1, Supporting Information). [ 38 ] We found that S, Se, and K compositions are distinctly varied in AAS/ICP‐OES results. As shown in Figure S4 in the Supporting Information, the top layer of the unmodified film is enriched with Se, which shows a similar trend with the In composition distribution.…”
Section: Resultsmentioning
confidence: 94%
“…RSF is calculated by integrating the total ion intensity from the D‐SIMS profile and dividing this value by the atomic concentration, which in turn was derived from the measurements of the atomic absorption spectroscopy (AAS) and inductively coupled plasma‐optical emission spectroscopy (ICP‐OES) (Table S1, Supporting Information). [ 38 ] We found that S, Se, and K compositions are distinctly varied in AAS/ICP‐OES results. As shown in Figure S4 in the Supporting Information, the top layer of the unmodified film is enriched with Se, which shows a similar trend with the In composition distribution.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure 4b,c, [ 33 ] atomic composition profiles are produced by dividing the D‐SIMS or AES profiles by the relative sensitivity factor (RSF). [ 66 ] The RSF is determined by integrating the total ion intensity of the profile and dividing this by the atomic concentration obtained using atomic absorption spectroscopy (AAS) and inductively coupled plasma‐optical emission spectroscopy (ICP‐OES). Ga/(Ga + In) and S/(S + Se) depth profiles are produced from the atomic concentrations and bandgap ( E g ) depth profiles are calculated from the atomic ratio using Equation () (Figure 4d) [ 62 ] leftEnormalgCuInGaSSe X, Y=1Y false[1XEnormalgCuInSSeY+XEnormalgCuGaSSe(Y) bCuInGaSeX1Xfalse]+Yfalse[1XEnormalgCuInSSeY+XEnormalgCuGaSSeY bCuInGaSX1Xfalse] where X = Ga/(Ga + In), Y = S/(S + Se), and b is the optical bowing constant for the corrections.…”
Section: Characterization Of Crystal Ordering Morphology and Compositionmentioning
confidence: 99%
“…Although the depth distributions of the two elements are not uniform, the relative mole fractions of Ag and Cu can be determined by comparison of total quantity (atoms cm −2 ) of each element determined by ion scattering simulations of the integrated peak intensities of Ag and Cu [23,24]. This method to determine the average mole fractions is the same methodology as the ID ICP-MS where the average mole fractions are obtained from the relative amounts of Ag and Cu dissolved in the solution.…”
Section: Quantification By Meismentioning
confidence: 99%